Case reportBrachytherapy as a treatment for malignant melanoma of the nasal cavity and nasopharynx – case report - Scepanovic, Danijela; Paluga, Marek; Rybnikarova, Michaela; Pobijakova, Margita; Masarykova, Andrea; Kroslak, Milan (Journal of Contemporary Brachytherapy, 2013)
Purpose : Primary malignant melanoma of the nasal cavity and nasopharynx is rarely seen. Clinically, most patients display initial nonspecific symptoms of unilateral nasal obstruction or epistaxis. The prognosis is generally poor, with a mean survival time of 3.5 years. Material and methods: In this paper, we have reported the case of malignant melanoma of the nasal cavity and nasopharynx. 79 years old man had presented with the swelling of the nose, nasal blockage and epistaxis during the six months before diagnosis. Functional endoscopic sinus surgery was performed to excised the nasal cavity tumor. Using positron emission tomography/computed tomography examination with 18-fluorodeoxyglucose, the patient was diagnosed with residual nasopharyngeal tumor after surgery. Results: Following the diagnosis, intracavitary brachytherapy for nasopharynx was administered. Solitary cervical nodal involvement occurred 6 months after the diagnosis when had been completely removed. After that, external beam radiotherapy was performed on the submandibular area on the right side. Thereafter, the patient was given follow-up care in the Department of Radiation Oncology until the time of distant progression of the disease. Conclusions : We have chosen to discuss this condition, because of its rarity and the possibility of using radiotherapy, even though the malignant melanoma had been regarded as a radioresistant disease, and also to emphasize the importance of a multidisciplinary approach to treatment of such patients.